(untitled) (Research, Society and Development, 2021)
The distance and social isolation adopted as some of population protection measures during the COVID-19 pandemic imposed adaptations in the teaching and learning dynamics. In response to the challenges that arose, educational institutions and, in particular, teachers and students previously used to face-to-face teaching, envisaged the alternative of remote teaching. In this context, we report here a remote teaching experience that occurred during the first year of the pandemic, in which it was perceived that it was impossible to carry out face-to-face classes at a school in the rural area of Minas Gerais, an opportunity to develop and use multipurpose material to be used in remote as well as face-to-face teaching. The material, created with the aim of promoting student autonomy with the help of the teacher, inserts themes related to solar physics within the scope of physics topics covered in basic education. The experience was successful in promoting the students’ expected attitudes as can be seen from the reports of the students themselves who participated in the teaching activities.